2020
DOI: 10.1016/j.jep.2020.112932
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential treatments of COVID-19 from Traditional Chinese Medicine (TCM) by using a data-driven approach

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 17 publications
2
85
0
Order By: Relevance
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“…Vast amount of in silico VS studies against SARS-CoV-2 Mpro has been reported over past months 26-30, 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . As the detailed description on the molecular modeling studies is out of Scope for this current communication, readers interested in learning more about recent molecular modeling studies to identify probable CoV protease inhibitors are directed to mentioned references 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72...…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“…The results of frequency analysis and association rule analysis indicated that Gancao was the key medicine of these formulae for the epidemic disease treatment, which was consistent with the previous data mining study [12] . In TCM practice, Gancao is described as “National Venerable Master” and is usually used in the combination with other CMMs in many formulae to harmonize the properties of other herbs, alleviate their toxicity and modulate the taste of the formulae due to its sweet flavor [13] , which can support the high frequency of Gancao in these formulae.…”
Section: Resultsmentioning
confidence: 99%
“…The Huangqin extract can also inhibit the replication of the influenza virus in mice [44] . Various compounds in Gancao, Huangqin, Chaihu , have been proved to have the potential to directly inhibit papain-like protease and 3C-like protease, which are essential for the replication of the pathogen SARS-CoV-2 that causes COVID-19 [ 12 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to find out the potential Chinese medicines or active ingredients against COVID-19, scholars used data mining and network to mine the high-frequency Chinese medicines and formulas from ancient prescriptions, then explored binding rates between the main ingredients in high frequency Chinese medicines and the key targets of SARS-COV-2 via using molecular docking approach. Finally, a network pharmacology was used to uncover the potential molecular mechanism [ 81 ]. Researchers can quickly screen out potential medicines by CADD, but further animal experiments and clinical studies should be performed to confirm the safety and effectiveness of these medicines.…”
Section: Discussionmentioning
confidence: 99%